On the Generation of a Class of Einstein-Maxwell Solutions - Halilsoy, Mustafa (General Relativity and Gravitation, Springer, 1983)
We make an alternative approach to Bonnorification by making use of effective Lagrangians for the gravitational fields. Using this technique we obtain a new Einstein-Maxwell solution
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1007/BF00761577) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: general relativity; gravitational waves; Einstein-Maxwell solution